The Use of Garlic as Feed Additive in Local Concentrate Feed for Goats on In Vitro Digestibility of Dry Matter and Organic Matter - Hakim Mita Arifa; Khasanah Ummul; Rifai Ahmad; Jamila Jamila; Syahrir Syahriani; Natsir Asmuddin (BIO Web of Conferences)
The study aimed to determine the effect of garlic (Allium sativum) as an herbal additive in goat concentrate feed made from local feedstuff on in vitro digestibility of dry matter and organic matter. The study was conducted using a completely randomized design with 5 treatments and 3 replications. Treatment T0 = control, T1 = concentrate feed + 0.025% garlic powder, T2 = concentrate feed + 0.05% garlic powder, T3 = concentrate feed + 0.075% garlic powder, T4 = concentrate feed + 0.1% garlic powder. The analysis of variance showed that the effect of giving garlic (Allium sativum) in goat concentrate feed made from local feedstuff had a significant effect (P<0.05) on dry matter and organic matter digestibility. The results showed that the addition of 0.1% garlic in goat concentrate made from local feedstuff increased in vitro digestibility of dry matter and organic matter.